Self-Harm Measurements - Mashudi, Sugeng; Isroin, Laily; Alwi, Aslan (The Health Researcher's Journal, 2024)
Background: Self-harm could be a basic nursing mental health issue for adolescents/young grown-ups. Aims: The purpose of this study is to explain the self-harm measurement tool. Method: Four databases were systematically searched (Google Scholar, PubMed, Scopus and Web of Science). Results and Discussion: Eight frequently used self-harm assessment tools were identified and assessed for risk of bias, criteria for good measurement properties, and quality of evidence using the COSMIN checklist. Of these, two tools had sufficient evidence of internal consistency (ISAS, QNSSI), and one had been frequently used with adults (NSSI-AT). Conclusion: These five tools may have the potential for use in adults for content validity and measurement properties in the general population.